2011
DOI: 10.4028/www.scientific.net/amr.188.469
|View full text |Cite
|
Sign up to set email alerts
|

Tools Optimization in Efficient Intermittent Cutting of 2.25Cr1Mo0.25V Steel

Abstract: In order to improve the machining efficiency of high strength steel 2.25Cr1Mo0.25V and tool life, intermittent turning performance of 2.25Cr1Mo0.25V with common carbide tools and advanced coated carbide tools was experimentally studied, cutting parameters and tool types were optimized. The results showed that the machining efficiency and tool life of advanced coated carbide tools were remarkably higher than that of common carbide tool; the tool life of quadrate coated tool was longer than that of circular tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The analysis of (MRR) was not considered, as it is calculated based on the input variables through equation ( 1), which is utilized in multi-objective optimization. The primary impacts of (Ra) and (Pm) are depicted in Figure (4). It is evident that the factor with the steepest slope exerts the most significant influence on the examined output parameter.…”
Section: Anova For Different Responsesmentioning
confidence: 97%
See 1 more Smart Citation
“…The analysis of (MRR) was not considered, as it is calculated based on the input variables through equation ( 1), which is utilized in multi-objective optimization. The primary impacts of (Ra) and (Pm) are depicted in Figure (4). It is evident that the factor with the steepest slope exerts the most significant influence on the examined output parameter.…”
Section: Anova For Different Responsesmentioning
confidence: 97%
“…H.L. Liu et al [4] carried out an experimental study in (IT) of 2.25-Cr-1Mo-0.25V steel employing a specified cutting tool (YT5) alongside an alternative (GC4235). The found results revealed the effectiveness of the (GC4235) tool compared to the (YT5) tool.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the increased cutting temperature softens the workpiece. Liu et al [4] conducted experiments in (IT) using two different cutting tools (YT5 and GC4235) on high-strength steel 2.25Cr1Mo0.25V. The results obtained showed that at low cutting speeds, the predominant wear form of cemented carbide YT5 is flank wear, but at high cutting speeds, the predominant wear form is breakage, and tool life is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The results prove that increasing the nitride content induces a decrease in Ra and VB. Liu et al [6] performed experiments in IT of 2.25Cr1Mo0.25V steel with two different cutting tools of YT5 and GC4235. The obtained results showed that the tool performance GC4235 is superior to the tool YT5.…”
Section: Introductionmentioning
confidence: 99%